(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2013)
B. F. Skinner (1904-1990) is frequently cited as having a contrary position on the use of aversive control. However, in certain passages Skinner presents a more flexible opinion about the use of this type of behavioral control. The purpose of the present study was to identify and analyze the passages where Skinner prescribes or warns about such use. A conceptual study was conducted involving eight Skinner works (Skinner 1938/1991, 1948/1975, 1953/1989, 1968/1972, 1969/1980, 1971, 1974/2006, 1989), analyzed according to the following categories: 1) the definition of aversive control and concepts involved; 2) the negative aspects of aversive control and prohibitions; and 3) the positive aspects of aversive control and its recommendations. It wasn’t possible to find a specific definition of aversive control and it was observed that at certain moments Skinner justifies the use of aversive control, but does not prescribe it in general